Perumusan Strategi Digital UMKM Indonesia Berbasis Rasionalitas Ekonomi Adaptif: Literature Review - Hartawan Hartawan; Didiek Harry Setyawan; Adi Penawan; Sutariyani Sutariyani (STIE AUB Surakarta, 2026)
This research aims to formulate a digital strategy for Indonesian MSMEs based on adaptive economic rationality through a synthesis of literature on digitalization and economic decision-making. This study uses a non-systematic literature review approach to 21 Scopus-indexed journal articles that discuss the adoption of TAM, TOE, and TRA-based technologies, Resource-Based View perspectives and dynamic capabilities, as well as issues of digital financial inclusion, AI and big data, gender, and sustainability. The data is analyzed through conceptual extraction and thematic synthesis to identify patterns of change in economic rationality in the context of digital transformation. The results of the study show a shift from instrumental rationality based on financial calculation to rationality influenced by technological perception, social norms, organizational readiness, adaptive capabilities, institutional legitimacy, and dependence on digital platforms. The literature also shows the emergence of a hybrid economic rationality that combines financial considerations, social value, sustainability, and data utilization. The conclusion of this study confirms that digitalization not only has an impact on the performance of MSMEs, but also reshapes the logic of economic decision-making. This research contributes by integrating various theoretical perspectives in one framework of adaptive economic rationality as the basis for the formulation of the digital strategy of Indonesian MSMEs.